Strategi Komunikasi Pemasaran Melalui Strorytelling Perumahan Grand Citra Mandiri dalam Membangun Koneksi Emosional dengan Pembeli - Ardana, Anna Fitri (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the implementation of storytelling in property marketing communication at PT Cahaya Bangun Bersaudara. Using a qualitative descriptive approach, the research provides an in-depth description of how the marketing team employs various communication strategies to convey the value of homes and build emotional attachment with prospective buyers. Storytelling is applied through verbal narratives emphasizing themes of family, future, security, and comfort, positioning the home not merely as a physical asset but as a meaningful living space for its occupants. In addition, product visualization, such as brochures, floor plans, 3D images, and sample units, is used to reinforce the verbal narrative, helping potential buyers imagine life within the property. Nonverbal communication by the marketing team, including gestures, facial expressions, and empathetic behavior, also plays a crucial role in establishing trust and emotional closeness with buyers. The findings indicate that the combination of verbal narratives, product visualization, and nonverbal communication effectively enhances emotional engagement, strengthens consumer trust, and influences home purchasing decisions. Therefore, storytelling proves to be an effective marketing communication strategy, supporting the success of face-to-face property sales while strengthening the emotional bond between consumers and the offered product.